2019
DOI: 10.1002/esp.4583
|View full text |Cite
|
Sign up to set email alerts
|

Holocene Dune Activity in the Thar Desert, India

Abstract: The Thar Desert dune system in north‐west India and eastern Pakistan provides a rich archive of past environmental, geomorphological and climatic change. Much of the knowledge about the timing of dune accumulation in the Thar stems from scattered and sporadic records, based on older luminescence dating protocols. If the Thar dune record is to be incorporated within a growing multiproxy framework of past climate and environmental dynamics, it is necessary to generate a systematic record of the timing of dunefie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…The organic content by weight is less than 2 %, while carbonate content by weight increases with depth in a section, varying between ~1 and ~5 %. These organic and carbonate values are consistent with other recently reported values from Thar parabolic dune sands (Srivastava et al, 2019). distributions for the majority samples in this study ranges between 20 % and 45 % (Table 2), with slightly higher values (~45%) observed for two of the younger samples.…”
Section: Sedimentologysupporting
confidence: 93%
See 3 more Smart Citations
“…The organic content by weight is less than 2 %, while carbonate content by weight increases with depth in a section, varying between ~1 and ~5 %. These organic and carbonate values are consistent with other recently reported values from Thar parabolic dune sands (Srivastava et al, 2019). distributions for the majority samples in this study ranges between 20 % and 45 % (Table 2), with slightly higher values (~45%) observed for two of the younger samples.…”
Section: Sedimentologysupporting
confidence: 93%
“…As a result, almost a third of the luminescence ages from drylands listed in the INQUA dune database are from linear dunes (Lancaster et al, 2016). In contrast, there are no ages in the database from linear dunes in the Thar Desert because the majority of chronometric studies to date have focussed on parabolic dunes (Thomas et al, 1999; 4 Kar et al, 2001;Singhvi and Kar, 2004;Dhir et al, 2010;Srivastava et al, 2019). The aim of this work therefore, is to apply a spatially intensive sampling strategy and modern luminescence dating techniques to develop a linear dunefield chronology from the Thar and integrate it into existing knowledge of the geomorphic evolution of the Thar dunes and regional palaeoenvironmental interpretations arising from such results.…”
Section: And the Central Thar Nearmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, a recent paper (Srivastava et al, 2019a), based on few OSL dates on five parabolic sand dunes in the Jodhpur-Shergarh-Dechu tract, claimed to have identified several Holocene dunebuilding phases which they alleged our OSL-based data could not. To clarify the issue we provide here a summary of the major Holocene aeolian sand accumulation phases identified by them vis-a-vis our data (Table 1).…”
Section: Sampling Strategy and Its Implicationsmentioning
confidence: 91%